2020
DOI: 10.3390/rel11080405
|View full text |Cite
|
Sign up to set email alerts
|

How Does Religion Affect Giving to Outgroups and Secular Organizations? A Systematic Literature Review

Abstract: Although religious giving represents the largest sector of charitable giving in the US, its overall impact on social welfare has been questioned, pointing to the possibility that the majority of funding might stay within the religious community, with little benefit to outgroups or secular charity. Despite multiple studies showing a positive relationship between religion and secular and outgroup giving, some empirical findings show a negative or non-significant relationship. By employing a systematic literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…For instance, Kuran (2018) reviewed the literature concerned with Islam and economic performance and concluded that Muslim's charity benefits mostly the middle and upper middle classes and not the poor. Yasin et al (2020) examined charitable giving outside religious communities and found non-negligible heterogeneity across studies. They attributed this heterogeneity to differences in location, operationalization of religion, and the methodology used.…”
Section: The Poor Versus the Poorestmentioning
confidence: 99%
“…For instance, Kuran (2018) reviewed the literature concerned with Islam and economic performance and concluded that Muslim's charity benefits mostly the middle and upper middle classes and not the poor. Yasin et al (2020) examined charitable giving outside religious communities and found non-negligible heterogeneity across studies. They attributed this heterogeneity to differences in location, operationalization of religion, and the methodology used.…”
Section: The Poor Versus the Poorestmentioning
confidence: 99%
“…Scholars have developed only a partial understanding of how differences in religious tradition influence giving outside of congregations (Yasin et al, 2020). The scholarship on the relationship between religious tradition and disaster response is even thinner.…”
Section: Congregational Characteristics As Predictors Of Giving and V...mentioning
confidence: 99%
“…This implies that organizations are competing for essential resources from a finite pool.” Much of the research on giving focuses on whether those who are religious, in addition to donating to their own religious organizations, also donate more money to secular or out-group organizations than the non-religious. In Yasin, Adams, and King ( 2020 ) review of the literature on the relationship between religiosity and giving to out-groups, they identified that most studies found a positive relationship between religiosity and charitable giving to out-group organizations. Numerous studies of social movements have found positive associations between external organizational affiliations and participation in a social movement or protest (Corcoran et al 2011 , 2015 ; Kitts 1999 ; McAdam 1986 ; Passy and Giugni 2001 ; Schussman and Soule 2005 ; Somma 2010 ; Walsh and Warland 1983 ) even when the external organizational affiliations are other social movement organizations (Kitts 1999 ).…”
Section: Multiple Congregational Attendancementioning
confidence: 99%